2019
DOI: 10.1177/1479973119872513
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of Pseudomonas aeruginosa with inhaled colistin in adults with non-cystic fibrosis bronchiectasis

Abstract: The persistent isolation of Pseudomonas aeruginosa in the airways of non-cystic fibrosis bronchiectasis (NCFB) patients is associated with a worsening of the symptoms, increase of exacerbations, poor quality of life and functional impairment. The objective of this study was the analysis of the eradication rate of P. aeruginosa in the sputum of patients with NCFB treated with inhaled colistin and the effects of the treatment in the exacerbations. This was a prospective, cohort, study of 67 NCFB patients treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…It also found a long time period prior to the next exacerbation. Similarly, another uncontrolled study [178] showed a significant reduction in both exacerbations and hospital admissions.…”
Section: Responses To the Treatment Of Primary Chronic Bronchial Infementioning
confidence: 77%
See 1 more Smart Citation
“…It also found a long time period prior to the next exacerbation. Similarly, another uncontrolled study [178] showed a significant reduction in both exacerbations and hospital admissions.…”
Section: Responses To the Treatment Of Primary Chronic Bronchial Infementioning
confidence: 77%
“…The few studies undertaken with inhaled colistin included no more than 30 patients each [173,175,176], and only one [173] had an eradicative program involving systemic antibiotics (its eradication rate was 43% at 14 months). One 12-month prospective cohort study with a protocol for the eradication of P. aeruginosa comprising the administration of systemic antibiotics followed by inhaled colistin (Promixin 1 MIU twice daily administered via I-neb ® ; Philips Respironics, Chichester, UK) [178] reported eradication rates of 61.2%, 50.7%, 43.3%, and 40.3% after 3, 6, 9, and 12 months of treatment, respectively.…”
Section: Responses To the Treatment Of Primary Chronic Bronchial Infementioning
confidence: 99%
“…Inhaled colistin realized eradication rates of P. aeruginosa of 61.2, 50.7, 43.3, and 40.3% after respectively 3, 6, 9, and 12 months of treatment. 106 Also, a significant reduction in the number of exacerbations was observed, 104 and a statistically significant difference in time to exacerbation in favor of the treatment group when poorly adherent patients were excluded from the analysis. 107 Overall, the recent ERS 69 and BTS 42 guidelines recommend the long-term use of inhaled antibiotics for patients with bronchiectasis, chronic P. aeruginosa infection and frequent pulmonary exacerbations (conditional recommendation, moderate quality evidence).…”
Section: Inhaled Antibioticsmentioning
confidence: 92%
“…US Cystic Fibrosis National Patient Registry data (Figure 2) show a shift away from aminoglycoside alone (81% in 2009 to 50.7% in 2016) and increasing use of monobactams such as aztreonam (3.7% to 43.2% in the same period). All three antibiotics have been independently linked to increased lung function, increased body weight and reduced need for hospitalisation [98][99][100][101]. Additionally, the treatment regimen has changed to one of rotation of antibiotic therapies to reduce the emergence of resistance.…”
Section: Antibioticsmentioning
confidence: 99%
“…All three antibiotics have been independently linked to increased lung function, increased body weight and reduced need for hospitalisation [ 98 , 99 , 100 , 101 ]. Additionally, the treatment regimen has changed to one of rotation of antibiotic therapies to reduce the emergence of resistance.…”
Section: Current Treatments For Bacterial Infection In Cfmentioning
confidence: 99%